Estimation of femoral neck bone mineral density by ultrasound scanning: Preliminary results and feasibility. (December 2016) - Pisani, Paola; Conversano, Francesco; Chiriacò, Fernanda; Quarta, Eugenio; Quarta, Laura; Muratore, Maurizio; Lay-Ekuakille, Aimè; Casciaro, Sergio
Highlights: The feasibility of a new ultrasound approach for femoral densitometry was demonstrated. The diagnostic agreement with the reference gold standard resulted very good. The proposed approach has the potential to be employed for osteoporosis diagnosis. Abstract: Aim of this paper was to assess the diagnostic accuracy of a novel ultrasound (US) approach for femoral neck densitometry. A total of 173 female patients (56–75 years) were recruited and all of them underwent a dual X-ray absorptiometry (DXA) of the proximal femur and an US scan of the same anatomical district. Acquired US data were analysed through a novel algorithm that performed a series of spectral and statistical analyses in order to calculate bone mineral density employing an innovative method. Diagnostic accuracy of US investigations was quantitatively assessed through a direct comparison with DXA results. The average diagnostic agreement resulted pretty good (85.55%), with a maximum (88.00%) in correspondence of the youngest investigated patients (56–60 y). Overall, diagnostic accuracy showed only minimal variations with patient age, indicating that the proposed approach has the potential to be effectively employable for osteoporosis diagnosis in the whole considered age interval.